Graphene oxide-based SPR biosensor chip for immunoassay applications - Chiu, Nan-Fu (Springer, 2014)
This work develops a highly sensitive immunoassay sensor for use in graphene oxide sheet (GOS)-based surface plasmon resonance (SPR) chips. This sensing film, which is formed by chemically modifying a GOS surface, has covalent bonds that strongly interact with the bovine serum albumin (BSA), explaining why it has a higher sensitivity. This GOS film-based SPR chip has a BSA concentration detection limit that is 100 times higher than that of the conventional Au-film-based sensor. The affinity constants (K(A)) on the GOS film-based SPR chip and the conventional SPR chip for 100 μg/ml BSA are 80.82 × 10(6) M(-1) and 15.67 × 10(6) M(-1), respectively. Therefore, the affinity constant of the GOS film-based SPR chip is 5.2 times higher than that of the conventional chip. With respect to the protein-protein interaction, the SPR sensor capability to detect angle changes at a low concentration anti-BSA of 75.75 nM on the GOS film-based SPR chip and the conventional SPR chip is 36.1867 and 26.1759 mdeg, respectively. At a high concentration, anti-BSA of 378.78 nM on the GOS film-based SPR chip and the conventional SPR chip reveals two times increases in the SPR angle shift. Above results demonstrate that the GOS film is promising for highly sensitive clinical diagnostic applications.